Low-Intensity Transcranial Ultrasound Stimulation Inhibits Epileptic Seizures in Motor Cortex by Modulating Hippocampus Neural Activity - Na Pang; Qianqian Wang; Jiamin Pei; Hailin Zhang; Yi Yuan; Jiaqing Yan (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Prior studies indicate that applying low-intensity transcranial ultrasound stimulation (TUS) to the hippocampus can suppress epileptic seizures. Nevertheless, it is unclear how TUS regulates hippocampal neural activity, and whether and how epileptic discharges in the motor cortex are suppressed by modulating hippocampal neural activity. To explore the answers of above questions, ultrasound was utilized to investigate the responses to the aforementioned inquiries by stimulating the hippocampus of mice with penicillin-induced epilepsy, while simultaneously recording the local field potentials (LFPs) in the hippocampus and the motor cortex (M1) throughout the experiment. The results showed that TUS: 1) reduced the amplitude and the strength of the $\boldsymbol {θ } $ frequency band in LFPs in the hippocampus and M1; 2) decreased the coupling strength of the $\boldsymbol {δ }$ - $\boldsymbol {γ } $ , $\boldsymbol {θ } $ - $\boldsymbol {γ }$ and $\boldsymbol {α } $ - $\boldsymbol {γ } $ frequency bands in the hippocampus and M1; and 3) weakened the correlation of neural activity between the hippocampus and M1. The above results indicated that TUS effectively suppressed abnormal slow neural oscillations in the hippocampus, had a significant decoupling effect on slow-fast neural oscillations, and reduced the correlation of hippocampus-cortical neural activity. TUS of the hippocampus may be through the hippocampus-cortical circuits to suppress abnormal neural firing activity in M1.